An Investigation About Some Difficulties Encountered by Libyan University First Year Students in Writing English Paragraphs via Computers, A Comparative Case Study between the Traditional Way and the Modern Way of Writing English Paragraphs - Hneesh, Marwa Issa; Albawe, Fawzia Abugela Salem; Asheny, Abugela Abdulah (Advances in Social Sciences Research Journal, 2018)
English writing is one of the most important means of communication and contacting today, it is necessary to maintain this skill correct and professional. The students have to develop their communicative skills, especially writing skills. Effectively, for those who wish to be professional persons in their lives, and also for their higher studies.